Análisis del modelo pedagógico de inicial II del Centro Infantil Primero de Mayo - Guevara Valdivieso, Michelle Carolina (2018)
The present paper is about pedagogical models in initial education and the model that works the Children's center first of May, located in the south of the city of Quito. By observing the teacher, it could be felt as it develops its class, and thus determine the model that is using. In addition, it allowed to verify whether there is coherence of the model proposed by the institution with the observed. The research is structured by a theoretical foundation which presents concepts of initial education. Where, the pedagogical models of initial education and general pedagogical models are detailed. In addition, it details the methodology used for the collection of data of the work, in which was used a record of Journal of field that allowed to describe each one of the classes of the teacher. Finally, a presentation and analysis of the findings that help to determine the activities that the teacher does and if they are aligned with the model of the institution and that of the initial education curriculum are made.